Low‐dose ketamine affects blood pressure, but not muscle sympathetic nerve activity, during progressive central hypovolemia without altering tolerance. (20th October 2020) - Huang, Mu; Watso, Joseph C.; Moralez, Gilbert; Cramer, Matthew N.; Hendrix, Joseph M.; Yoo, Jeung‐Ki; Badrov, Mark B.; Fu, Qi; Hinojosa‐Laborde, Carmen; Crandall, Craig G.
Abstract : Key points: Haemorrhage is the leading cause of battlefield and civilian trauma deaths. Given that a haemorrhagic injury on the battlefield is almost always associated with pain, it is paramount that the administered pain medication does not disrupt the physiological mechanisms that are beneficial in defending against the haemorrhagic insult. Current guidelines from the US Army's Committee on Tactical Combat Casualty Care (CoTCCC) for the selection of pain medications administered to a haemorrhaging soldier are based upon limited scientific evidence, with the clear majority of supporting studies being conducted on anaesthetized animals. Specifically, the influence of low‐dose ketamine, one of three analgesics employed in the pre‐hospital setting by the US Army, on haemorrhagic tolerance in humans is unknown. For the first time in conscious males and females, the findings of the present study demonstrate that the administration of an analgesic dose of ketamine does not compromise tolerance to a simulated haemorrhagic insult. Increases in muscle sympathetic nerve activity during progressive lower‐body negative pressure were not different between trials. Despite the lack of differences for muscle sympathetic nerve activity responses, mean blood pressure and heart rate were higher during moderate hypovolemia after ketamine vs . placebo administration. Abstract: Haemorrhage is the leading cause of battlefield and civilian trauma deaths. For a haemorrhaging soldier, there are several pain medications (e.g. ketamine) recommended for use in the prehospital, field setting. However, the data to support these recommendations are primarily limited to studies in animals. Therefore, it is unknown whether ketamine adversely affects physiological mechanisms responsible for maintenance of arterial blood pressure (BP) during haemorrhage in humans. In humans, ketamine has been demonstrated to raise resting BP, although it has not been studied with the concomitant central hypovolemia that occurs during haemorrhage. Thus, the present study aimed to test the hypothesis that ketamine does not impair haemorrhagic tolerance in humans. Thirty volunteers (15 females) participated in this double‐blinded, randomized, placebo‐controlled trial. A pre‐syncopal limited progressive lower‐body negative pressure (LBNP; a validated model for simulating haemorrhage) test was conducted following the administration of ketamine (20 mg) or placebo (saline). Tolerance was quantified as a cumulative stress index and compared between trials using a paired, two‐tailed t test. We compared muscle sympathetic nerve activity (MSNA; microneurography), beat‐to‐beat BP (photoplethysmography) and heart rate (electrocardiogram) responses during the LBNP test using a mixed effects model (time [LBNP stage] × drug). Tolerance to the LBNP test was not different between trials (Ketamine: 635 ± 391 vs . Placebo: 652 ± 360 mmHg‧min, p = 0.77). Increases in MSNA burst frequency (time: P < 0.01, trial: p = 0.27, interaction: p = 0.39) during LBNP stages were no different between trials. Despite the lack of differences for MSNA responses, mean BP (time: P < 0.01, trial: P < 0.01, interaction: p = 0.01) and heart rate (time: P < 0.01, trial: P < 0.01, interaction: P < 0.01) were higher during moderate hypovolemia after ketamine vs . placebo administration ( P < 0.05 for all, post hoc ), but not at the end of LBNP. These data, which are the first to be obtained in conscious humans, demonstrate that the administration of low‐dose ketamine does not impair tolerance to simulated haemorrhage or mechanisms responsible for maintenance of BP. Key points: Haemorrhage is the leading cause of battlefield and civilian trauma deaths. Given that a haemorrhagic injury on the battlefield is almost always associated with pain, it is paramount that the administered pain medication does not disrupt the physiological mechanisms that are beneficial in defending against the haemorrhagic insult. Current guidelines from the US Army's Committee on Tactical Combat Casualty Care (CoTCCC) for the selection of pain medications administered to a haemorrhaging soldier are based upon limited scientific evidence, with the clear majority of supporting studies being conducted on anaesthetized animals. Specifically, the influence of low‐dose ketamine, one of three analgesics employed in the pre‐hospital setting by the US Army, on haemorrhagic tolerance in humans is unknown. For the first time in conscious males and females, the findings of the present study demonstrate that the administration of an analgesic dose of ketamine does not compromise tolerance to a simulated haemorrhagic insult. Increases in muscle sympathetic nerve activity during progressive lower‐body negative pressure were not different between trials. Despite the lack of differences for muscle sympathetic nerve activity responses, mean blood pressure and heart rate were higher during moderate hypovolemia after ketamine vs . placebo administration.